2019
DOI: 10.21608/ejnf.2019.75842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Nano-Zinc and Nano-Selenium Addition on Productive and Physiological Performance of Growing Rabbits at Fattening Period

Abstract: his study was designed to evaluate the effects of dietary Nano-zinc (Nano-Zn) and Nano-selenium (Nano-Se) supplementation on growth performance, nutrients utilization, carcass parameters and blood plasma biochemical in growing rabbits. A total of 50, six-week-old New Zealand White (NZW) rabbits of about 815 g l.b.w. were randomly distributed into five equal groups. The control group was fed on a basal diet without any supplement; the second and third groups were fed the basal diet supplemented with 30 and 60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…It also protected the intestinal mucosa and improved its absorptive capacity, preventing diarrhea by decreasing the peristastic movement of the intestine [ 35 ]. In contrast to our results, of Abdel-Wareth et al [ 16 ], Tag-El Din [ 24 ], and El-Kazaz et al [ 36 ] revealed that nano-Se reduced the TFI in growing NZW rabbits, male Californian rabbits, and Japanese quails, respectively. Such variations may be attributed to using different doses, sex, or species.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It also protected the intestinal mucosa and improved its absorptive capacity, preventing diarrhea by decreasing the peristastic movement of the intestine [ 35 ]. In contrast to our results, of Abdel-Wareth et al [ 16 ], Tag-El Din [ 24 ], and El-Kazaz et al [ 36 ] revealed that nano-Se reduced the TFI in growing NZW rabbits, male Californian rabbits, and Japanese quails, respectively. Such variations may be attributed to using different doses, sex, or species.…”
Section: Discussioncontrasting
confidence: 99%
“…Se is a crucial element that regulates the body’s energy, protein anabolism, and oxidative stress, allowing animals to develop and reproduce normally [ 28 ]. However, recent research reveals that the NRC Se standard of 0.08 mg/kg in a developing rabbit diet failed to meet the rabbit’s growth requirements and that high levels are required to optimize nutrient digestion, absorption, and utilization, which boosts productive and reproductive performance [ 13 , 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It includes the formation and control of particles at “nanoscale” having novel and improved physicochemical properties. Recent study has shown that mineral nanoparticles have greater bioavailability due to their new characteristics, such as greater specific surface area, high catalytic efficiency, higher surface activity, and stronger adsorbing ability, as well as it may be readily carried up by the gastrointestinal tract and used in the animal system and reached to deeper tissues by high efficient than the larger-sized particles (Tag-ElDin 2019 ).…”
Section: Introductionmentioning
confidence: 99%